Neither inaccurate nor biased in later life: Age-related differences in the accuracy and bias of facial trustworthiness judgment - Atsunobu Suzuki; Kenta Ishikawa; Matia Okubo (Proceedings of the National Academy of Sciences, 2025)
People tend to form impressions of others’ trustworthiness based on their facial appearance and make trust-related decisions accordingly. In such face-based trustworthiness judgments (FBTJs), older adults are generally more likely than younger adults to attribute higher trustworthiness. This pattern is sometimes referred to as positivity bias and has been proposed as a potential risk factor for fraud victimization in later life. However, previous studies lack objective ground-truth measures of the actual trustworthiness of FBTJ targets, thus limiting their ability to assess the accuracy and bias of such judgments. To address this gap, we conducted three studies to examine age-related differences in FBTJ accuracy and bias using behavior in a trust game (Studies 1 and 2, Japanese participants) and records of political corruption convictions (Study 3, British participants) as ground-truth indicators of trustworthiness. In participant-level analyses, older adults demonstrated either higher accuracy (Studies 1 and 3) or comparable accuracy (Study 2) relative to younger adults. Furthermore, younger adults consistently tended to judge others as untrustworthy; however, older adults did not exhibit this negativity bias (Studies 1 and 2), and only a milder positivity bias emerged in Study 3. Although these age-related differences, particularly in accuracy, became less evident when face-level variability was considered, the overall results suggest that older adults perform as well as, or even better than, younger adults in terms of FBTJ accuracy and bias. This finding challenges the conventional view that older adults’ FBTJs are positively distorted and increase their vulnerability to deception.